Analysis Of The Influence Of Umrah Travel Services, Prices And Facilities On Umrah Pilgrimage Satisfaction In Medan City - Taufiq, Taufiq; Batubara, Maryam; Arif, Muhammad (UNIVERSITAS PAKUAN, 2023)
With the increasing development of the times, service to customers is a very important factor. Therefore, the provider must be able to provide satisfaction to its customers, for example by providing a higher quality, cheaper product and better service. A product is said to be of good quality if it can meet the needs of its customers. Therefore, knowledge of customer needs and satisfaction (customer requirements) is very important. In this study using quantitative methods with a sample of 85 Umrah pilgrims in Medan City. The results of this study show that service has a significant effect on pilgrim satisfaction. The processed data showed that the sig value was 0.019 0.05. It means that Ho is rejected and Ha is accepted. Thus, it can be concluded that there is a positive and significant influence between services on the satisfaction of Umrah pilgrims in Medan City. Cost has a significant effect on pilgrim satisfaction. The results showed that 0.029 0.05. It means that Ho is rejected and Ha is accepted. There is a positive and significant influence between costs on the satisfaction of Umrah pilgrims in Medan City. Facilities have a significant effect on pilgrim satisfaction. The results showed that 0.018 0.05. That is, Ho was rejected, Ha accepted. There is a positive and significant influence between facilities on the satisfaction of Umrah pilgrims in Medan City.